THE WOMAN AS REACTION TO TRAUMA IN A PATRIARCHY - VAIDEHI 'S AKKU (A MEMORY CALLED AMMACHI) - Rekha, (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This research investigates the relation between trauma and women by analyzing Vaidehi's Akku in A Woman Called Ammachi. It seeks to understand how the prevailing norms of masculinity further adds to the already existing emotional bankruptcy, causes greater mental harm, and discourage the pursuit of assistance. Using qualitative secondary study, the research emphasizes the narrative of Akku as the case of women who are subjugated by the systems. The paper suggest that women’s trauma cannot be healed without the abolition of the patriarchal ways of thinking and the empowerment of females. This study explains how feminists need to take up the themes of trauma, self-empowerment and recollection as a source of strength.